A comparative study, between China and Portugal, of the professional training of the master’s course in translation - Hu, Zhihua; Roberto, Maria Teresa (Millenium - Journal of Education, Technologies, and Health, 2019)
Introduction: With globalization, the interdependence of skills and domains has deepened worldwide. The training of competent translators is becoming more and more important. In 2007, the Chinese Academic Degree Commission began the implementation of the MTI (Master’s in Translation and Interpreting). So far, more than 200 universities have already received the qualification to start this course. Unlike the academic masters’, the MTI is a professional master’s degree, with the objective of training competent translators so that, after training, they can adapt quickly to the demands of the labour market. Objectives: Due to the late start and little experience in this area, despite the very rapid growth of the number of universities with MTI, the translators trained in this master’s course do not have the skills required by the labour market. For the time being, the level of MTI training in China is still very far from the foreign mature models, which resulted in this comparative analysis, between China and Portugal, of the master’s degree in translation. According to Nord (2006), besides the translation skill, there are also linguistic, cultural, professional, and technical skills. During training the focus should mainly be on the translation, professional and technical skills. In fact, Nord created the textual analysis model, emphasizing the importance of the analysis and of the decision concerning the internal and external factors to the texts. This way, she made the suggestions for the steps to be followed in the training of translators, clarifying the intercultural character of the translation and the roles of translators. Methods: Based on Nord’s (2006) theoretical model concerning the training of translators, a comparative study is carried out between the master’s course in translation in China and Portugal. Specifically, the objectives and the study plans of both masters’ courses will be studied, analyzing the differences and similarities with regard to the training of future professionals. Results: In this paper we compare the curricular plans of the three study cycles of Chinese and Portuguese universities, regarding translation, linguistic, cultural, professional and theoretical competences. Conclusions: We hope that this research can become an incentive for new policy making in education, contributing to the increase of practical and specialized teaching in students who wish to become a translator.